2012
DOI: 10.1021/ja3031449
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of High-Performance Oxygen Reduction Reaction Pt Electrocatalyst Supported on Reduced Graphene Oxide/Carbon Black Composite

Abstract: Oxygen reduction reaction (ORR) catalyst supported by hybrid composite materials is prepared by well-mixing carbon black (CB) with Pt-loaded reduced graphene oxide (RGO). With the insertion of CB particles between RGO sheets, stacking of RGO can be effectively prevented, promoting diffusion of oxygen molecules through the RGO sheets and enhancing the ORR electrocatalytic activity. The accelerated durability test (ADT) demonstrates that the hybrid supporting material can dramatically enhance the durability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
296
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(301 citation statements)
references
References 39 publications
5
296
0
Order By: Relevance
“…[4][5][6] Recently, graphene sheets, atomic layers of graphitic carbons, are demonstrated to possess twice higher capacity of graphitic carbons, and exhibit some unique features such as superior electrical conductivity, high surface area, structural fl exibility and chemical stability. [7][8][9][10][11][12][13][14][15] These features render graphene sheets to become a potential anode material for lithium storage. Moreover, both theoretical and experimental studies reveal that heteroatom (B, N, P and F)-doping of graphene can change their adsorption energy, the diffusion and desorption barrier of lithium ions, [16][17][18][19] which result in the enhanced reversible capacity for lithium storage with respect to pristine graphene.…”
Section: Doi: 101002/admi201300149mentioning
confidence: 99%
“…[4][5][6] Recently, graphene sheets, atomic layers of graphitic carbons, are demonstrated to possess twice higher capacity of graphitic carbons, and exhibit some unique features such as superior electrical conductivity, high surface area, structural fl exibility and chemical stability. [7][8][9][10][11][12][13][14][15] These features render graphene sheets to become a potential anode material for lithium storage. Moreover, both theoretical and experimental studies reveal that heteroatom (B, N, P and F)-doping of graphene can change their adsorption energy, the diffusion and desorption barrier of lithium ions, [16][17][18][19] which result in the enhanced reversible capacity for lithium storage with respect to pristine graphene.…”
Section: Doi: 101002/admi201300149mentioning
confidence: 99%
“…Severe stacking of GR sheets leads to a loss of the ultrahigh surface area advantage as a two-dimensional nanomaterial. Recently, a few efforts have been made to prevent GR sheets from severe stacking (Yoo, Kim, et al 2008;Park et al 2011;Li et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] 15,[18][19][20] To fundamentally solve this technological issue and improve electrocatalyst durability, alternative carbon-free electrocatalyst support materials such as tin oxide (SnO 2 ) 21-29 and titanium oxide (TiO x ) [30][31][32][33][34] have also been proposed. It has been shown that SnO 2 is a promising alternative platinum support, since it has good electronic conductivity and thermochemical stability under the strongly acidic cathode conditions in a PEFC.…”
mentioning
confidence: 99%